Climate Change Vulnerability Assessment of Patuakhali Municipality in Bangladesh (The Dhaka University Journal of Earth and Environmental Sciences, 2022)
Climate change will create adversative impact on the growth and development of future cities due to the proliferation of the extreme events, which will increase human, social, and economic losses over time. Therefore, it is necessary to move towards sustainable urbanization processes to reduce the impact of climate change. This research is aimed at carrying out climate change vulnerability assessment (CCVA) for Patuakhali Municipality, which is one of the most vulnerable municipalities in Bangladesh located in the southcentral coastal region of Bangladesh. The vulnerability of the study area is derived by overlaying the factor maps using equal class interval weighted index (ECIWI) and principal component analysis (PCA). Both methods show similar results in case of exposure and adaptive capacity assessment, but the results of vulnerability assessment are slightly different for some of the wards due to variation in the level of sensitivity obtained from two different methods. ECIWI and PCA show that Ward 9 and Ward 1 are the most and least vulnerable wards, respectively. Although exposure to hazards is similar in the study area, the degree of sensitivity and adaptive capacity for these two areas are different, which mainly contributes to their vulnerability. CCVA will help the local government to build resilience for the urban poor to reduce climate change-induced vulnerability, which can be utilized by the policymakers to increase awareness and to mitigate risk through planned interventions.The Dhaka University Journal of Earth and Environmental Sciences, Vol. 10(3), Special Issue 2022: 187-198